2016
DOI: 10.1177/1932296816667748
|View full text |Cite
|
Sign up to set email alerts
|

Use of Color Range Indicator Technology on Point-of-Care Meters May Ease Self-Management of Blood Glucose

Abstract: After attending this year's 4th Artificial Pancreas Workshop at the National Institutes of Health, 1 I was inspired by one of the panelists' comments on the tools available to people with diabetes. The individual, a person with type 1 diabetes who also happened to be an industrial design professional, criticized the manufacturers for deficiencies in the user interface of various technologies used by people with diabetes. This is not surprising to those of us who are innovators, clinicians or researchers in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…3 Others have observed that more appropriate decisions are made when BGMs display information that prompts users toward more favorable diabetes management decisions. 4 This is important given in a study of BG perceptions only 28% of patients considered results >235 mg/dl as high. 5 Another study found 56% of patients did not respond regularly to out-of-range BG readings with any self-care adjustments.…”
Section: Original Articlementioning
confidence: 99%
“…3 Others have observed that more appropriate decisions are made when BGMs display information that prompts users toward more favorable diabetes management decisions. 4 This is important given in a study of BG perceptions only 28% of patients considered results >235 mg/dl as high. 5 Another study found 56% of patients did not respond regularly to out-of-range BG readings with any self-care adjustments.…”
Section: Original Articlementioning
confidence: 99%
“…10-12 Evidence indicates that the use of a CRI-based GM improves the health literacy by engaging the patients in SMBG, and therefore, acting in a timely manner on blood glucose level. 13…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Evidence indicates that the use of a CRI-based GM improves the health literacy by engaging the patients in SMBG, and therefore, acting in a timely manner on blood glucose level. 13 A recent randomized control trial (RCT)-ACCENTScompared CRI-based GMs (OneTouch Verio Flex (Flex) and OneTouch Verio (Verio), LifeScan, Wayne, PA, United States) with GMs without CRI to analyze the impact of CRI on glycemic control in patients with type 1 and type 2 diabetes mellitus (T1DM and T2DM). The RCT demonstrated a statistically significant and clinically meaningful reduction (0.36%) in HbA1c when using Flex and Verio meters in patients with T1DM and T2DM.…”
Section: Introductionmentioning
confidence: 99%